2021
DOI: 10.1371/journal.pone.0256578
|View full text |Cite
|
Sign up to set email alerts
|

Patient prioritisation methods to shorten waiting times for elective surgery: A systematic review of how to improve access to surgery

Abstract: Background Concern about long waiting times for elective surgeries is not a recent phenomenon, but it has been heightened by the impact of the COVID-19 pandemic and its associated measures. One way to alleviate the problem might be to use prioritisation methods for patients on the waiting list and a wide range of research is available on such methods. However, significant variations and inconsistencies have been reported in prioritisation protocols from various specialties, institutions, and health systems. To… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
0
18
0
1
Order By: Relevance
“…Prioritizing patients on waiting lists has been recognized by several authors either by assigning surgical priority according to indications or using tools to help quantify prioritization [ 8 , 11 13 ]. Such tools often encompass patient factors, time spent on waiting list, and surgical factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prioritizing patients on waiting lists has been recognized by several authors either by assigning surgical priority according to indications or using tools to help quantify prioritization [ 8 , 11 13 ]. Such tools often encompass patient factors, time spent on waiting list, and surgical factors.…”
Section: Discussionmentioning
confidence: 99%
“…All patients listed for knee arthroplasty are not equal and priority four will not be applicable to all patients [ 10 ]. Objective prioritization of patients is difficult, and authors have suggested prioritizing according to scores, applied ethics, and knee-specific function [ 8 , 11 13 ]. Prior studies have identified which patients may benefit from a total knee arthroplasty (TKA).…”
Section: Introductionmentioning
confidence: 99%
“…9 Patients are commonly prioritized according to the time they have spent on a waiting list and/or surgical factors. [10][11][12][13] However, patients most in need of expeditious surgery may not receive it if this criterion is applied. Currently, surgical procedures are categorized as outlined above.…”
mentioning
confidence: 99%
“…In the literature [ 8 , 12 , 34 ], average waiting time has been considered important measure to evaluate the performance of the waiting list. It was found that there was appreciable reduction of 30.4% (from 4.246 days to 2.956 days) in the average wait time ( ) when the waiting list is prioritized.…”
Section: Discussionmentioning
confidence: 99%